Prevalence of Anemia and Iron Deficiency among Palestinian Pregnant Women and Its Association with Pregnancy Outcome - Mahmoud A. Srour; Samah S. Aqel; Khaled M. Srour; Khalid R. Younis; Fekri Samarah (Anemia)
Background. Anemia is a public health problem especially among pregnant women. This study aimed to investigate the prevalence of anemia and iron deficiency among pregnant women and its association with pregnancy outcome in Hebron Governorate in southern Palestine. Methods. This is a cross-sectional study that included 300 pregnant women in their first trimester and 163 babies. Maternal anthropometric and socioeconomic and newborns’ data were collected. Complete blood count for study subjects and maternal serum ferritin were measured. Results. The prevalence of iron deficiency anemia among pregnant women was 25.7% and 52% of them had depleted iron stores. When pregnant women were grouped into three hemoglobin (Hb) tertile groups, a significant difference was observed between maternal Hb and newborns’ birth weight (P= 0.009), height (P= 0.022), head circumference (P= 0.017), and gestational age (P= 0.012). There was a significant association between maternal serum ferritin and frequency of low birth weight (P= 0.001) and frequency of preterm delivery (P= 0.003). No significant association was observed between maternal anthropometric measures or the socioeconomic status and pregnancy outcomes. Conclusion. Iron deficiency is a moderate public health problem among the study subjects. Maternal Hb and serum ferritin significantly affect pregnancy outcomes.